Identification and validation of specific B-cell epitopes of hantaviruses associated to hemorrhagic fever and renal syndrome. - Fernando de Paiva Conte; Bianca Corrêa Tinoco; Thiago Santos Chaves; Renata Carvalho de Oliveira; Janaina Figueira Mansur; Ronaldo Mohana-Borges; Elba Regina Sampaio de Lemos; Patricia Cristina da Costa Neves; Rodrigo Nunes Rodrigues- (Public Library of Science (PLoS), 2019)
BACKGROUND:Orthohantavirus infection is a neglected global health problem affecting approximately 200,000 people/year, spread by rodent hosts and associated to fatal human diseases, such as hemorrhagic fever with renal syndrome (HFRS) and orthohantavirus cardiopulmonary syndrome (HCPS). Circulation of HFRS-associated orthohantaviruses, such as Seoul, Gou, Amur, Dobrava and Hantaan, are supposed to be restricted to Eurasian countries even though their hosts can be a worldwide distribution. Few confirmed HFRS orthohantavirus infections in humans have been reported in American countries, but due to lower medical awareness of the symptoms of this zoonosis, it could be associated to viral underreporting or to misdiagnosis with several tropical hemorrhagic diseases. Serological evidence of orthohantavirus infections, using enzyme-linked immunosorbent assay for the presence of immunoglobulin M and G against recombinant nucleoprotein protein, remains as an essential assay for viral surveillance. In this study, we aimed to identify in silico immunogenic B-cell linear epitopes present on orthohantavirus nucleoprotein that are exclusive to HFRS-related species. METHODOLOGY/PRINCIPAL FINDINGS:In silico analysis were performed using Seoul orthohantavirus nucleoprotein (SHNP) sequence as a model. Linear B-cell-epitopes on SHNP and its immunogenicity were predicted by BepiPred-2.0 and Vaxijen algorithms, respectively. The conservancy of predicted epitopes was compared with the most clinically relevant HFRS or HCPS-associated orthohantavirus, aiming to identify specific sequences from HFRS-orthohantavirus. Peptide validation was carried out by ELISA using Balb/c mice sera immunized with purified recombinant rSHNP. Peptides cross-reactivity against HCPS orthohantavirus were evaluated using immunized sera from mice injected with recombinant Juquitiba orthohantavirus nucleoprotein (rJHNP). CONCLUSION/SIGNIFICANCE:In silico analysis revealed nine potential immunogenic linear B-cell epitopes from SHNP; among them, SHNP(G72-D110) and SHNP(P251-D264) showed a high degree of sequence conservation among HFRS-related orthohantavirus and were experimentally validated against rSHNP-IMS and negatively validated against rJHNP-IMS. Taken together, we identified and validated two potential antigenic B-cell epitopes on SHNP, which were conserved among HFRS-associated orthohantavirus and could be applied to the development of novel immunodiagnostic tools for orthohantavirus surveillance.